2022
DOI: 10.3389/fbioe.2022.1046147
|View full text |Cite
|
Sign up to set email alerts
|

An injectable hyperthermic nanofiber mesh with switchable drug release to stimulate chemotherapy potency

Abstract: We developed a smart nanofiber mesh (SNM) with anticancer abilities as well as injectability and fast recovery from irregular to non-compressible shapes. The mesh can be injected at the tumor site to modulate and control anticancer effects by loading the chemotherapeutic drug, paclitaxel (PTX), as well as magnetic nanoparticles (MNPs). The storage modulus of the mesh decreases when applied with a certain shear strain, and the mesh can pass through a 14-gauge needle. Moreover, the fibrous morphology is maintain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The EHDA processes mainly take advantage of the quick and simple interactions between the electrostatic energy and working fluids, by which the solvents can be repelled ( Abadi et al, 2022 ; Sivan et al, 2022a ; Chen et al, 2022 ; Han et al, 2022 ; Yao et al, 2023 ). Thus, to prepare solid products, first and foremost the solvents must be removed all at once during the working processes.…”
Section: Resultsmentioning
confidence: 99%
“…The EHDA processes mainly take advantage of the quick and simple interactions between the electrostatic energy and working fluids, by which the solvents can be repelled ( Abadi et al, 2022 ; Sivan et al, 2022a ; Chen et al, 2022 ; Han et al, 2022 ; Yao et al, 2023 ). Thus, to prepare solid products, first and foremost the solvents must be removed all at once during the working processes.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, The capacity of a polymer to dissolve in a water-based solution at a specific temperature is known as thermoresponsiveness since organic solvents are inappropriate for usage in biological environments ( Bordat et al, 2019a ). Utilizing stimuli-responsive polymers as intelligent systems for drug delivery has garnered a lot of attention in the last few years ( Chen et al, 2022 ). Two groups of these polymers can be distinguished: those with an upper critical solution temperature (UCST) and those with a lower critical solution temperature (LCST).…”
Section: Recent Progress On Electrospun Smart Nanofibers For Cancer T...mentioning
confidence: 99%
“…The drug release test showed that PTX was released from the mesh in a switchable “on-off” manner. While very little was released within the cooling phase, about 73% of the loaded PTX was released after eight cycles ( Chen et al, 2022 ). in another study, by electrospinning gelatin and PNIPAAm-NHS in a solution consisting of 1-ethyl-3-(3-dimethyl-aminopropyl)-1-carbodiimide hydrochloride (EDC) and N-hydroxy succinimide (NHS) as the cross-linking agents, a straightforward one-step method for creating in situ cross-linked PNIPAAm/gelatin nanofibers has been devised ( Fig.…”
Section: Recent Progress On Electrospun Smart Nanofibers For Cancer T...mentioning
confidence: 99%